A descriptive analysis of the replication applied in aquaponic experimental studies - A. Lennard, Wilson (International Journal of Environment, Agriculture and Biotechnology, 2020)
A literature search was performed via SCOPUS for publications between January 2000 and April 2020 that contained the keywords aquaponic and hydroponic. Sixty-one articles were identified that stated a comparison and a form of comparative statistical analysis was performed. These articles were identified via the principle author, year of publication, the system type tested (coupled or decoupled aquaponic; irrigated nutrient solution from a separated RAS), the number of treatments tested, the number of replicates applied to each treatment and the region or country within which the experiment was performed. An experimental comparison context was assigned to each study to identify the requirement for replication. Sixty-one percent (61 %) of all the studies were deemed to have applied no or incorrect replication (no or incorrect replication: 56 % of fully recirculating system studies, 100 % of decoupled system studies, 86 % of irrigated RAS water studies). In terms of the comparison context, 54 % of system comparison studies, 100 % of solution comparison studies and 63 % of plant component associated comparison studies, applied no or incorrect replication. The association between study location and the incidence of no or incorrect replication was also determined (Europe – 71 %, USA – 80 %, South America – 63 %, Australia – 33 %, West Asia – 5 %, South East Asia; including China – 20 % and South Asia – 14 %). An experimental replication decision matrix was developed to assist future aquaponic researchers in determining the application of correct replication and several example research articles were discussed to demonstrate and explain the correct and incorrect application of replication in experimental designs for aquaponic associated research studies.